HUBUNGAN MASYARAKAT DALAM MENINGKATKAN PARTISIPASI MASYARAKAT PADA KEGIATAN HAFLAHAH IMTIHAN - Mohammad Alfian; Abdul Wahid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem addressed in this study stems from the low level of participation by the community, parents, alumni, and local leaders in the haflah imtihan activities at Madrasah Aliyah Al Ghazali Pragaan, even though these events have strategic value for the legitimacy of education and the strengthening of social and religious networks. The objectives of this study are to describe the public relations strategies implemented, analyze their impact on participation levels, identify effective local cultural practices, and formulate evidence-based public relations policy recommendations. The research employs a qualitative approach with a case study design through in-depth interviews, participatory observation, and document analysis, analyzed interactively following the Miles, Huberman, and Saldaña model to obtain credible and contextual findings. The results of the study show that public relations strategies combine conventional approaches (visiting community leaders, physical invitations, and announcements through mosques) and digital approaches (WhatsApp, Instagram, and YouTube), which synergistically increase community participation by around 30% compared to the previous year. The integration of local cultural practices such as blessings, hadrah, and the involvement of religious leaders proved to strengthen the legitimacy and emotional attachment of residents to the madrasah. This communication model, which combines digital innovation and local traditions, is effective in building the madrasah's image as an adaptive institution rooted in community values, making it a relevant reference for Islamic educational institutions based on pesantren.